2005
DOI: 10.1186/1475-2875-4-41
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate plus sulfadoxine-pyrimethamine for treatment of uncomplicated Plasmodium falciparum malaria in Sudan

Abstract: Background: Early diagnosis and effective treatment with an appropriate drug form the main components of the World Health Organization's strategy to reduce malaria related mortality. The few available drugs might be safeguarded if combined with artesunate. The addition of artesunate to a standard antimalarial treatment substantially reduces treatment failure, recrudescence and gametocyte carriage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Consistent with a recent study, the present study showed that P. vivax is a health problem and that its ratio to P. falciparum has increased [8]. Previous studies showed that AL had a high efficacy (98.7%) for treatment of uncomplicated P. falciparum malaria in eastern Sudan as well as other regions of the country [20,21]. Interestingly, in neighbouring Ethiopia, a higher failure rate was observed (19%) when AL was compared with chloroquine for treatment of uncomplicated P. vivax malaria [4].…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with a recent study, the present study showed that P. vivax is a health problem and that its ratio to P. falciparum has increased [8]. Previous studies showed that AL had a high efficacy (98.7%) for treatment of uncomplicated P. falciparum malaria in eastern Sudan as well as other regions of the country [20,21]. Interestingly, in neighbouring Ethiopia, a higher failure rate was observed (19%) when AL was compared with chloroquine for treatment of uncomplicated P. vivax malaria [4].…”
Section: Discussionsupporting
confidence: 90%
“…[59]. The base-line efficacy of AS/SP in eastern Sudan has been reported between 98 - 100% [56,60-62], while we have reported a base-line PCR corrected efficacy of 93% [57]. In the present study the in vivo per-protocol PCR corrected efficacy of AS/SP over 28 days is 90.5%.…”
Section: Discussionmentioning
confidence: 38%
“…The differences in the clinical response following treatment with chloroquine are likely due to elements of the host immunity and the prevalence of P. falciparum DNA polymorphisms [17]. Sudanese health authorities have updated malaria treatment in 2004 from chloroquine to artemisinin-based combination therapy (ACT) using the co-blister of artesunate + sulfadoxine/pyrimethamine and artemether + lumefantrine as first-and second-line, respectively [5]. Effects of the novel therapy regimen on erythropoiesis and red blood cell status still need to be clarified.…”
Section: Discussionmentioning
confidence: 99%